(untitled) (Persona y Derecho, 2018)
This paper reviews the main twentieth century changes that have shaped the contemporary crisis of identity. After exploring four hurricanes of modernity - total war; the cultural revolution of the 1960s; modernization and globalization; and the rise of the information society -I discuss the decline of trust in civil society. Personal identities once tightly focused on family, friends and neighborhood, are now much looser connections with the emphasis on social networking. The process is one of individualization, subjectivization, and self-realization. Collective identities are experiencing a crisis of legitimacy. ldeologies, associations, mainstream churches and nation-states have lost their mobilizing power. I argue that globalization in a network society offers a possible solution to the crisis. Until recently domestic and international politics, save in times of war, seemed separate worlds. In the twenty first century they form one continuum. Cosmopolitan politics with its advocacy of a global civil society offers not only an opportunity to reconnect individual and collective identities in a new and purposeful way but to respond to the demand for justice worldwide.